2006
DOI: 10.1074/jbc.m604772200
|View full text |Cite
|
Sign up to set email alerts
|

Cilia-like Structures and Polycystin-1 in Osteoblasts/Osteocytes and Associated Abnormalities in Skeletogenesis and Runx2 Expression

Abstract: We examined the osteoblast/osteocyte expression and function of polycystin-1 (PC1), a transmembrane protein that is a component of the polycystin-2 (PC2)-ciliary mechano-sensor complex in renal epithelial cells. We found that MC3T3-E1 osteoblasts and MLO-Y4 osteocytes express transcripts for PC1, PC2, and the ciliary proteins Tg737 and Kif3a. Immunohistochemical analysis detected cilia-like structures in MC3T3-E1 osteoblastic and MLO-Y4 osteocyte-like cell lines as well as primary osteocytes and osteoblasts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
260
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(275 citation statements)
references
References 58 publications
14
260
0
1
Order By: Relevance
“…(77) Activating Nek8 mutations lead to increased primary cilia length in the kidney, (28,77) whereas loss of function mutations in PKD1 induce PKD, skeletal defects in vivo, and decreased osteoblast differentiation in vitro. (78,79) As primary cilia may be part of the mechanosensing machinery that influences bone remodeling via b-catenin signaling, (80) NEK8 mutations in jck could theoretically influence the onset of HTO bone disease. However, tibia and femur length and total body weight were not different between 6-week-old WT and jck mice before the onset of renal dysfunction indicating that the mutation had no influence on normal growth (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…(77) Activating Nek8 mutations lead to increased primary cilia length in the kidney, (28,77) whereas loss of function mutations in PKD1 induce PKD, skeletal defects in vivo, and decreased osteoblast differentiation in vitro. (78,79) As primary cilia may be part of the mechanosensing machinery that influences bone remodeling via b-catenin signaling, (80) NEK8 mutations in jck could theoretically influence the onset of HTO bone disease. However, tibia and femur length and total body weight were not different between 6-week-old WT and jck mice before the onset of renal dysfunction indicating that the mutation had no influence on normal growth (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In several but not all respects, these abnormalities are reminiscent of those seen in developing Ihh -/-long bones (St-Jacques et al, 1999), pointing to the pivotal nature and general requirement of hedgehog action in skeletogenesis. Given their roles in hedgehog signaling, primary cilia should be as essential for skeletal development and growth as hedgehog proteins, and previous genetic studies certainly support that premise (Murcia et al, 2000;Olsen et al, 2005;Xiao et al, 2006;Zhang et al, 2003). In particular, limb and cranial skeletal abnormalities were found in conditional mouse mutants deficient in Kif3a or in the ciliaassociated mechanosensory protein polycystin-1 (Pkd1), as well as in mice bearing a missense mutation in the Pkd1 gene (Olsen et al, 2005;Xiao et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Given their roles in hedgehog signaling, primary cilia should be as essential for skeletal development and growth as hedgehog proteins, and previous genetic studies certainly support that premise (Murcia et al, 2000;Olsen et al, 2005;Xiao et al, 2006;Zhang et al, 2003). In particular, limb and cranial skeletal abnormalities were found in conditional mouse mutants deficient in Kif3a or in the ciliaassociated mechanosensory protein polycystin-1 (Pkd1), as well as in mice bearing a missense mutation in the Pkd1 gene (Olsen et al, 2005;Xiao et al, 2006). A more extensive recent study indicated that long bone anlagen in mouse embryo limbs deficient in Ift88 or Kif3a (prx1cre;Ift88 fl/n or prx1cre;Kif3a fl/n ) are short, exhibit accelerated chondrocyte hypertrophy and lack an intramembranous bone collar (Haycraft et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The classically recognized one is the role as mechanosensors, which is accomplished by translating mechanical stimuli into biochemical signals, which are then transferred to the other cells by means of the cellular processes [39]. This function requires the involvement of a protein complex, composed by the cilium and the cilia-associated proteins PolyCystin 1 and 2 [40].…”
Section: Osteocytes: Buried Alivementioning
confidence: 99%